Harvest estimates of the Western Arctic caribou herd, Alaska - Sutherland, Bob (Rangifer, 2005)
A generalized least squares regression model was developed to estimate local harvest of the Western Arctic caribou (Rangifer tarandus granti) herd. This model provides herd and community level harvest based on community size, proximity of the herd to the village. The model utilizes community harvest survey information from the Alaska Department of Fish and Game, Subsistence Division and cooperation from the nonprofit organizations Maniliq and Kawerak. The model will assist in an annual selection of communities to survey. The predicted local resident harvest of the Western Arctic caribou herd is 14 700 with 95% lower and upper confidence limits of 10 100 and 19 700 respectively.